A Existência das obras performáticas de Berna Reale e Lúcia Gomes nas coleções de Jorge Alex Athias e no Fundo Z - Casa das Onze Janelas em Belém do Pará - CABRAL, Marcela Guedes (Universidade Federal do Pará, 2024)
This research aims to understand how collecting occurs, specifically, the preservation of information and the poetics of performance art, through the acquisition and production of documentation of these works, which allows the existence of the work in several modes, allowing it to be included in public and private collections. Specific objectives: verify the representation of the intrinsic and extrinsic information of these artistic processes adopted by the artists and in the two collections developed; understand how the acquisition of scientific works occurred and the impact of this procedure on the preservation of information from these works, investigate how documentation, or its lack, allowed or not the preservation of artistic works of an ephemeral nature, and verify the perspectives from the collector and representatives of the institution about the presence of performances in the collection. For empirical observation, the research focuses on the work of two artists from Pará who expressively produce works of performance art and on two collections, in the city of Belém-PA, one public and the other private - where the works of the two artists were exhibited, namely, Berna Reale and Lúcia Gomes in the Fundo Z Collection of Casa das Onze Janelas, public, and in the Jorge Alex Athias Art Collection, private. Considering that contemporary works of art of a performative nature, such as performance and happenings, challenge museum professionals in their preservation actions through the documentation of information and poetics developed by artists, we understand that it is necessary to investigate the prospects for this type of preservation, with the support of art discourse enunciators and institutions that produce discourses about art. Therefore, this research is configured as an associative analysis with a qualitative approach. It adopts a theoretical-empirical and associative perspective between the process of musealization of work performance art of two artists in two collections, one public and the other private. It also involves on-site observation of the documented process of the artists in the Collections, as well as analysis of the documentation, intrinsic and extrinsic information, and the discourses about and by the artists. Semi-structured interviews are also used with the artists, the collector and the professionals at Casa das Onze Janelas.